Almost lacunary statistical and strongly almost lacunary convergence of sequences of fuzzy numbers - Gokhan, Ayseguel; Et, Mikail; Mursaleen, Mohammad (Pergamon-Elsevier Science Ltd, 2009)
The purpose of this paper is to introduce the concepts of almost lacunary statistical convergence and strongly almost lacunary convergence of sequences of fuzzy numbers. We give some relations related to these concepts. We establish some connections between strongly almost lacunary convergence and almost lacunary statistical convergence of sequences of fuzzy numbers. It is also shown that if a sequence of fuzzy numbers is strongly almost lacunary convergent with respect to an Orlicz function then it is almost lacunary statistical convergent. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fuzzy numbers; Statistical convergence; Lacunary sequences; Orlicz function